Analysis of Star Catalog Model Based on The Nearest Star Composition and Brightest Star as Guide Star - Ramadhana, Alif; Saifudin, M A; Poetro, Ridanto E; Fathurahim, L (International Journal of Aviation Science and Engineering - AVIA, 2024)
Star sensor is the most advanced attitude determining instrument for spacecraft with very high accuracy, and it is independent of other attitude sensors. However, the star sensor's accuracy and processing time depend on selecting the algorithm, which starts from detecting the star pattern until the matching process with the star catalog. The star catalog consists of the right ascension and declination of stars' position and magnitude for 250.000 stars which need a large memory size. Therefore, modifying a new star catalog consisting of guide stars' position,magnitude, and nearest star composition can reduce the required memory and processing time without losing accuracy. T he nearest star catalog model in this paper used radial based featurewhere for each guide star candidate, the number of stars in each binary (bin) layer around the guide star will be calculated. This paper focuses on determining the best architecture for the nearest star catalog model, such as the number of bin layers and bin ranges, and the influence ofstar sensor field of view and guide star limitation with the model's accuracy. The proposed star catalog provides excellent performance in low-cost star sensors with a high and medium field of view.